Bases for a Latin American response to the international economic crisis - Carlos Alzamora; Enrique V. Iglesias (CEPAL Review, 1983)
On 11 February 1983, the President of Ecuador, His Excellency Dr. Osvaldo Hurtado, sent us a letter in which, after emphasizing the seriousness of the present international economic situation, he noted that “the world has not known such a serious and prolonged crisis since the Great Depression of the 1930s”.